Heat treatment and characterization of Yb doped barium cerate prepared via sol-Gel technique - Nafisah Osman; Ibrahim Abu Talib; Hamidi Abd. Hamid (Universiti Kebangsaan Malaysia, 2009)
The BaCe0.95Yb0.05O2.975 compound was successfully prepared by the sol-gel method using metal acetate salts as starting materials. Fourier transform infrared (FTIR) results showed that the carbonate ions residue almost disappeared at calcination temperature of 1300ºC. Particles size of the final calcined powder obtained from particle size distribution was in the range of 300 – 450 nm. Diameter of grains for the sintered pellet (relative density !85%) obtained from scanning electron microscope was between 2 – 5 μm. It is interesting to note that eliminating the carbonate ions residue enhanced the mechanical and chemical stability of the sample.